CubeSat: LEO mission control unit potential communication concept for AMR system - Yahya, A.S.; Hashim, Wahidah; Ismail, Ahmad Fadzil; Sulaiman, S.H.; Sulaiman, M.F. (Blue Eyes Intelligence Engineering & Sciences Publication, 2018)
The dramatic drop in equipment pricing, better services and efficiency of small satellite candidate is an interesting communication technology alternative for the deployment of Smart Grid (SG). The use of commercial-off-theshelf (COTS) components and the ongoing miniaturiza-tion of several technologies have already led to scattered instance of mission with promising scientific value. In this paper, the potential of Low Earth Orbit (LEO) Mission Control Unit (MCU) for small class satellite payloads is presented with the goal of providing utilities in-dustry to low cost and efficiency system towards enhancement of the services provided. Many commercial companies have emerged to cater this objective, however most of them provide an expensive LEO satellites solution. Therefore, this paper proposes a low cost and compact platform to substitute the conventional one. The proposed solution in this paper is targeting Automatic Meter Reading (AMR) system spe-cifically at rural area meter. In particular, this research is intended mainly for the researchers to start an exploration of new technology to be implemented in near future. Advanced development and assessment of CubeSats for SG will make it possible to be used as an alternative communication link.